On Polymer Expansion for Gibbsian States of Nonequilibrium Systems of Interacting Brownian Oscillators - Skrypnik, W.I. (Український математичний журнал, 2003)
The convergence of polymer cluster expansions for correlation functions of general Gibbs oscillator-type systems and related nonequilibrium systems of Brownian oscillators is established. The initial states for the latter are Gibbsian. It is proved that the sequence of the constructed correlation functions of the nonequilibrium system is a generalized solution of a diffusion BBGKY-type hierarchy.